PENDIDIKAN KARAKTER DALAM LARANGAN MENYEMBELIH SAPI (Menelisik Filosofi Ajaran Sunan Kudus) - Mahlail Syakur (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2021)
Islam as a part of the social system comes with a mission as rahmah lil-‘alamin to take part in nation-building. On the other sides Indonesia is a multicultural country where Islam is one of the subsystems. Therefore, Islam should be introduced as the potential for an inclusive, democratic and pluralist. Sunan Kudus spreads Islam by way of acculturation traditions and local culture because at that time the majority of the population is Hindu Holy.This research includes the study of literature (library research) using the method of documentation and descriptive. Descriptive method is used to describe all of the information about the fatwa Sunan Kudus and his background. The researcher also used a historical approach to photographing the events of the past time.There are two findings in this study, namely: (1) Prohibition of slaughtering cows that produce discourse that the Kudus people have high awareness for religious tolerance when Islam was come to Kudus, (2) Character education in banning slaughter cows produced a discourse that architecture of Mosque and Kudus Minaret and fatwa "Prohibition of slaughtering cows" contains the educational value of inter-religious tolerance.Methods and strategies of propaganda Sunan Kudus conceived a view to educating the Muslim community in order to have a noble character, are willing to respect and appreciate the confidence the Hindu community who believed that the cow is considered sacred animals.